PEMBENTUKAN KARAKTER ANAK MELALUI KEGIATAN MENDONGENG - Danny, Desy Ery (Faculty of Humanities, Diponegoro University, 2013)
ABSTRACT This study aimed to examine the extent to which story can shape a person's character. This study uses descriptive qualitative analysis with case studies. This study uses data collection through observation, library research and interviews. Informant who used the qualifications of three people with early adulthood (20-40 years) and adults (40-60 years). The analysis showed that the story is an effective medium of cognitive development, the child will do the stages of attention, remember, and reproduce motion motivated from the message of stories that have told, through tale children's character can be formed continuously so that the selection story of the materials of story should be made to foster a positive message child's emotions and thoughts. The conclusion of this study is the message when the story is told from childhood capable individual stored either in memory and can be equipped to live as adults. Keywords: Character, story